RP-HPLC Estimation of Valacyclovir in Tablets - N. Rao, Pilli; Raja Rajeswari, K.; Jayathirtha Rao, V.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2010)
A simple, reliable and reproducible HPLC method has been developed for the analysis of valacyclovir in tablet dosage forms. Chromatography was carried out on a C18 column using phosphate buffer-acetonitrile (30 : 70 v/v) as the mobile phase at a flow rate of 1 mL/min. Adenine was used as an internal standard. Detection was carried out at 230 nm. Linearity was observed in the concentration range 5-60 μg/mL of valacyclovir with a limit of detection of 5 ng/mL. Parameters of validation obtained prove the precision of the method and its applicability for the determination of valacyclovir in tablet formulations.